El bosque en la ciudad: la invención del urbanismo moderno en la Ciudad de México (1870-1930) - Alfonso Valenzuela Aguilera (Les Cahiers ALHIM)
The beautification and sanitation of cities of the early twentieth century in Latin America not only sought to liberate them from epidemics that plagued most of the European and Latin American capitals, but such interventions materialized the aura of progress, positioning the cities at international competitive standards as well as stressing the supremacy of knowledge. The participation of Miguel Angel de Quevedo, developer, engineer and environmentalist who developed a series of visionary proposals to conserve, improve and enhance the environmental quality of the city proposals are analyzed. We argue that emerging metropolis became one of the main tools of modernization using international standards where Quevedo sought to establish environmental planning as a discipline in Mexico. The paper concludes that despite a period of intense social and political turmoil, Quevedo stands out as one of the leading environmentalist shaping the modernization of Mexico City in collaboration with different groups of power, while demonstrating the successful transfer of urban planning ideas worldwide.